Discussion - Of Mr. Blake's Paper on Superficial Blackening and Discoloration of Rocks, Especially in Desert Regions (see p. 371) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
Theo. B. ComstocK, Los Angeles, Cal. (communication to the Secretary*):—Mr. Blake's recent paper upon this topic undoubtedly partly explains the rationale of a part of the known facts bearing upon discolorat'ion and encrustation of rocks. His quotation from Humboldt, with reference to certain South American examples, may be questioned in the light of further facts, which do not appear to bear out the great traveler's theory of causation. There is no available evidence that the waters of the tropical rivers referred to by Professor Blake contain dissolved organic matter in the varying proportions required to demonstrate Humboldt's guess, nor do the concomitant facts in any manner bear out the hypothesis that the blackening in one case and its absence in the other may, perhaps, be traced to differences in the chemical reactions of the respective waters. Careful consideration of Professor Blake's illustrations, in connection with numerous personal observations extending over widely-scattered areas, convinces me that elements of